Cryo-CMOS Circuits and Systems for Quantum Computing Applications - Patra, Bishnu; Incandela, Rosario M.; van Dijk, Jeroen P. G.; Homulle, Harald A. R.; Lin Song; Shahmohammadi, Mina; Staszewski, Robert Bogdan; Vladimirescu, Andrei; Babaie, Masoud; Sebastiano, Fabio; Charbon, Edoardo (IEEE journal of solid-state circuits, 2018)
A fault-tolerant quantum computer with millions of quantum bits (qubits) requires massive yet very precise control electronics for the manipulation and readout of individual qubits. CMOS operating at cryogenic temperatures down to 4 K (cryo-CMOS) allows for closer system integration, thus promising a scalable solution to enable future quantum computers. In this paper, a cryogenic control system is proposed, along with the required specifications, for the interface of the classical electronics with the quantum processor. To prove the advantages of such a system, the functionality of key circuit blocks is experimentally demonstrated. The characteristic properties of cryo-CMOS are exploited to design a noise-canceling low-noise amplifier for spin-qubit RF-reflectometry readout and a class-F2,3 digitally controlled oscillator required to manipulate the state of qubits.